The Rules of Interpretation and Examples of Their Application - Huda, Miftahul; Reksiana (STKQ Al-Hikam Depok, 2025)
This article aims to comprehensively explain the meaning, history, and types of interpretive rules, along with examples of their implementation in interpreting the Qur'an. The research method employed is library research, examining authentic primary sources related to interpretive rules as the main foundation required for an interpreter. The results indicate that interpretive rules, known as qawa'id al-Tafsir, are basic guidelines generally applied to gain a deep understanding of Quranic instructions. Historically, the emergence of these rules as an independent science was pioneered by Ibn Taimiyah (661-728 H). This writing identifies eight distinct types of rules: the rules of the Qur'an, Sunnah, language, isytiqaq, balaghah, ushul fiqh, qira'at, and science. Furthermore, the article discusses the development of interpretive rules in the modern era, which utilizes the maudhu'i (thematic) method by significantly considering the socio-historical conditions faced by each interpreter today.